Symbolic CSR, Stakeholder Engagement, and Financial Performance: Evidence from Indonesian Mining Firms (2016–2020) - Sahat Parlindungan Simarmata (Politeknik Siber Cerdika Internasional, 2026)
Background: This study examines why CSR disclosure is associated with lower short-term accounting performance in the Indonesian mining sector after POJK 51/2017, drawing on stakeholder, agency, and institutional decoupling theories, with decoupling as the primary explanation. Objective: This study tests whether IC mediates the CSR–financial performance relationship, challenging the assumption that IC automatically transforms CSR into performance gains. Methods: A balanced panel of 44 out of 47 eligible IDX-listed mining firms (2016–2020; N = 139 firm-years; three firms excluded due to delisting or incomplete disclosures) was estimated using a fixed-effects model, selected over pooled OLS and random-effects models based on Chow and Hausman tests (chi-square = 58.05; p < 0.001). Results: CSR disclosure demonstrates a large and significant negative association with ROA (β = −0.969; p = 0.0018), remaining robust across five sensitivity checks, while IC (VAIC) emerges as the dominant positive driver of FP (β = +0.967; p < 0.001). Ownership concentration and board size show no robust effects, while IC does not mediate the CSR–FP relationship. This pattern, cautiously labeled the CSR Penalty, contributes by (i) documenting a substantial negative CSR effect among emerging-market extractive firms, (ii) refining the IC missing-link thesis by showing that IC is a strong direct but non-mediating driver, and (iii) linking these findings to the initial reporting cycle of POJK 51/2017. Conclusion: The findings confirm a CSR Penalty and non-mediating role of IC among Indonesian mining firms in 2016–2020, with conclusions limited to this sector and regulatory period.